Comprehensive Evaluation of (+)-Usnic Acid–induced Cardiotoxicity in Rats by Sequential Cross-omics Analysis. (June 2017) - Yokouchi, Y.; Imaoka, M.; Niino, N.; Kiyosawa, N.; Kai, K.
Two-week administration of (+)-usnic acid (UA) induces mitochondrial swelling of cardiomyocytes, and toxicogenomic analysis of the heart revealed upregulation of oxidative stress, amino acid limitation, and endoplasmic reticulum stress–related genes in rats. To analyze the pathogenesis, UA was orally administrated to rats for 1, 4, 7, and 14 days, and sequential histopathological, genomic, and metabolomic analyses were performed on the heart, liver, and plasma. As a result, mitochondrial swelling of cardiomyocytes was observed on day 15 preceded by genomic upregulation on days 5 and 8. Of the focused gene groups, amino acid limitation–related genes represented by Mthfd2 showed numerically higher values or upregulation from day 5, which was sustained through the experimental period. On the contrary, oxidative stress–related genes were upregulated temporally on day 5. In metabolomic analysis, amino acids such as taurocholate and their metabolites fluctuated in concert with the upregulation of amino acid limitation–related genes in the heart, liver, and plasma. Moreover, accumulations of bile acids were manifested in all the tested tissues, while no histopathological change was seen in the liver. Increased bile acids might have an indirect effect on the myocardium; however, more detailed analysis is required. In conclusion, amino acid limitation was suggested as the pivotal toxic trigger of UA-induced cardiotoxicity.